(untitled) (Italiano LinguaDue, 2022)
This essay documents the diffusion of the Italian language and culture in Aotearoa-New Zealand, an officially bilingual (English and Māori), as revealed by the double name, and multicultural society. By adopting an eclectic approach that combines sociolinguistics, language teaching methodology, and cultural anthropology, my paper is a micro-ethnography performed on a group of five women of Italian origin with different levels of competency in Italian as their second language. This group of Kiwis – as New Zealanders frequently refer to themselves – ranged age from 16 to 68 and reside in greater Auckland, New Zealand’s most populous city. Their testimonies were collected through a series of face-to-face semi-structured qualitative interviews and based on several sessions of participant observation involving immersion and interaction in the socio-cultural environment of the informants. Notwithstanding their small number, the stories collected in this research disclose a significant ethnographic relevance as they testify to key aspects of Italianness in the social and historical context of New Zealand. In line with the sociolinguistic theories on the circulation of Italian in the world, on the motivations underpinning its learning and on the typology of speakers, I specifically addressed the following topics: Italian as a language of migration, Italian as a language of culture, Italian taught at university, Italian as part of a fluid and transnational multi-identity, and Italian in the global market. Due metà dello stesso Kiwi: lingua e cultura italiana tra i neozelandesi di origine italiana Il seguente saggio documenta la diffusione della lingua e della cultura italiana in Aotearoa - Nuova Zelanda, paese ufficialmente bilingue (inglese e Māori), come rivela il doppio nome, e multiculturale. Attraverso un approccio eclettico che combina sociolinguistica, glottodidattica e antropologia culturale, l’articolo si propone come micro-etnografia condotta su un gruppo di cinque donne di origine italiana con diversi livelli di competenza in italiano come lingua seconda. Questo gruppo di informatrici Kiwi – questo è il nome con il quale i/le neozelandesi si riferiscono comunemente a sé stessi/e – ha un’età compresa tra i sedici e i sessantotto anni e risiede nell’area metropolitana di Auckland, la città più popolosa della Nuova Zelanda. Le loro testimonianze sono state raccolte tramite una serie di interviste qualitative semi-strutturate, condotte di persona, e diverse sessioni di osservazione partecipante che hanno comportato l’immersione e l’interazione nell’ambiente socio-culturale delle informatrici. Nonostante il loro numero limitato, le storie raccolte in questa ricerca dimostrano una significativa rilevanza etnografica poiché testimoniano aspetti chiave dell’italianità nel contesto storico-sociale neozelandese. In linea con le teorie sociolinguistiche sulla circolazione dell’italiano nel mondo, sui motivi dell’apprendimento e sulla tipologia dei parlanti, ho esaminato nello specifico i seguenti argomenti: l’italiano lingua di migrazione, l’italiano lingua di cultura, l’italiano insegnato all’università, l’italiano come parte di una pluri-identità fluida e transnazionale e, infine, l’italiano nel mercato globale.